Near-Peer Coaching to Enhance Operative Learning: An Educational Innovation for Surgical Training - Alexander J. Papachristos, MSurgicalEd; Elizabeth Molloy, PhD; Juanita N. Chui, MD; Monica Ghidinelli, PhD; Simon Kitto, PhD; Debra Nestel, PhD; Benjamin P. T. Loveday, PhD (Annals of Surgery Open)
Objective:. To design, implement, and evaluate a near-peer coaching model to enhance operative learning in general surgery training. Background:. There is an urgent need to maximize operative learning in surgical education. Trainees find barriers to operative learning difficult to navigate and often sacrifice educational opportunities for the sake of impression management. Methods:. A prospective cohort study was conducted over a 6-month period following design and implementation of a trainee-led near-peer coaching model; “SPICE” (Set goals, Plan, Imagine, Comment and feedback, Evaluate and reflect). Semistructured interviews were conducted to explore trainees’ experiences of the model. Results:. Twelve trainees participated in the study. The near-peer coaching encounters provided trainees with the psychological safety to be honest about learning needs, validated insecurities, and mitigated the pressures associated with impression management that consistently shaped consultant–trainee relationships. Trainees described improved operative performance, increased self-confidence, and a greater ability to adapt to the unexpected. Trainees adapted the use of the SPICE model to conventional consultant–trainee dynamics, which facilitated learning conversations and negotiation of operative opportunities. On a broader scale, trainees noticed an improvement in the teaching culture of the unit, describing that the use of the model legitimized the importance of perioperative learning conversations and increased consultant enthusiasm for teaching. Conclusions:. Near-peer coaching created a unique psychological safety that facilitated authentic reflection and goal setting and improved trainee confidence. The benefits of the SPICE model were translated to other contexts and facilitated entrustment in conventional consultant–trainee relationships.